1991
DOI: 10.1111/j.1525-1314.1991.tb00558.x
|View full text |Cite
|
Sign up to set email alerts
|

The smectite–chlorite transition in drillhole NJ‐15, Nesjavellir geothermal field, Iceland: XRD, BSE and electron microprobe investigations

Abstract: In well NJ-15 of the Nesjavellir geothermal field, Iceland, the transition of discrete smectite into discrete chlorite has been studied from drill cuttings recovered at depths of less than 1714 m and over a continuous range of temperatures between 60 and 300" C. At temperatures below 180" C, the clay fractions contain mixtures of di-and trioctahedral smectites, whose layer charge increases with depth. Between 200 and 240" C, discrete smectites have transformed into smectite-rich, randomly interstratified chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
153
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(158 citation statements)
references
References 27 publications
4
153
1
Order By: Relevance
“…These charaeteristics are different than those of most electron microprobe analyses of low-grade chlorite, for which significant octahedral vacancies are frequently reported (Hillier and Velde 1991), a relation implying contamination by interlayered phases that occur commonly in metabasites (Shau et al 1990;Schiffman and Fridleifsson 1991). These relations and the lack of stable equilibrium as generally recognized (Velde and Medhioub 1988;Peacor 1992;de Caritat et al 1993) and demonstrated above for the Gasp6 chlorite suggest that use of chlorite composition as a geothermometer in low-grade regimes (Cathelineau and Nieva 1985;Cathelineau 1988) is not warranted.…”
Section: Compositional Variation Of Chloritementioning
confidence: 50%
See 3 more Smart Citations
“…These charaeteristics are different than those of most electron microprobe analyses of low-grade chlorite, for which significant octahedral vacancies are frequently reported (Hillier and Velde 1991), a relation implying contamination by interlayered phases that occur commonly in metabasites (Shau et al 1990;Schiffman and Fridleifsson 1991). These relations and the lack of stable equilibrium as generally recognized (Velde and Medhioub 1988;Peacor 1992;de Caritat et al 1993) and demonstrated above for the Gasp6 chlorite suggest that use of chlorite composition as a geothermometer in low-grade regimes (Cathelineau and Nieva 1985;Cathelineau 1988) is not warranted.…”
Section: Compositional Variation Of Chloritementioning
confidence: 50%
“…The mixed-layer component is identified as C/S with ~ 60% chlorite and R 1 ordering based on the aforementioned features and peak positions. After heating at 375~ a significant decrease in the intensity of the ~ 14-~ reflection is associated with the addition of a high-20 shoulder, and the 7.51-,~ reflection like that shown in Figure 2 was shifted further toward the low 20 side in patterns of the diagenetic samples (Jiang 1993), typical of the characteristics of C/S (Bettison and Schiffman 1988;Schiffman and Fridleifsson 1991). In the pattern of the airdried specimen, the ~10-A peak of illite is slightly asymmetric and has a tail on the low 20 side.…”
Section: X-ray Powder Diffractionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the empirical calibration of Cathelineau and Nieva (1985), as revised by Cathelineau (1988), to estimate the temperature of equilibration of chlorite in the metasedimentary rocks of Hole 917A. As Schiffman and Fridleifsson (1991) cautioned, this thermometer should only be applied to nearly pure chlorites with very low amounts of interlayered smectite. Bettison and Schiffman (1988) showed that chlorite containing more than 6.25 Si cations per formula unit (based on 28 oxygens) include interlayered smectite.…”
Section: Metamorphic Processes and P/t Conditionsmentioning
confidence: 99%